2006
DOI: 10.1159/000095568
|View full text |Cite
|
Sign up to set email alerts
|

Primary Spinal Anaplastic Ganglioglioma

Abstract: Gangliogliomas of the spinal cord are very unusual and the anaplastic variant of these tumors is extremely rare. In spinal anaplastic gangliogliomas, malignant changes (hypercellularity, vascular proliferation, necrosis, high numbers of mitotic figures) are typically evident in the glial element of the tumor. Gangliogliomas can arise in any part of the central nervous system and the features of adult and pediatric cases differ significantly. We describe the case of a pediatric patient who had a spinal anaplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Four other case reports of pediatric primary spinal aGG were found in the literature, as follows: one comparable to the patient presented here with stable disease at 61 months after diagnosis but no information about her clinical status (table 1, gray shading) [4]; one patient with postoperative right leg palsy and a progression-free follow-up of 22 months [9]; one with progressive disease after 7 months [4], and one without information regarding outcome (high-grade tumor in a series of cerebral and spinal low-grade GGs that was not further discussed) [11]. In adult patients, 4 descriptions of primary intramedullary aGG were found [5,6,10,12].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Four other case reports of pediatric primary spinal aGG were found in the literature, as follows: one comparable to the patient presented here with stable disease at 61 months after diagnosis but no information about her clinical status (table 1, gray shading) [4]; one patient with postoperative right leg palsy and a progression-free follow-up of 22 months [9]; one with progressive disease after 7 months [4], and one without information regarding outcome (high-grade tumor in a series of cerebral and spinal low-grade GGs that was not further discussed) [11]. In adult patients, 4 descriptions of primary intramedullary aGG were found [5,6,10,12].…”
Section: Discussionmentioning
confidence: 96%
“…Usually, complete resection of low-grade tumors in children results in a favorable long-term oncologic outcome [14] and a favorable neurologic outcome when motor pathways remain intact [15]. However, the few anecdotal precedents of this rare tumor variant provided some evidence for an unfavorable outcome with surgical resection followed by either radio- or chemotherapy [1,4,5,6,7,8,9]. There is only one report of a long-term survivor in the pediatric population (table 1, gray shading), and this patient received combined adjuvant radiochemotherapy treatment [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy is generally given to patients with incomplete resection of the tumor or recurrent tumor, and to those with a tumor histology showing anaplastic features or oligodendroglial-like cells [6]. There are only a few reports of AGG of the spinal cord [1,2,3,4,5,6,7,8,9,10,11] (table 1). Blümcke and Wiestler [1] published a series of 326 gangliogliomas, only 17 of which were reported as AGG.…”
Section: Discussionmentioning
confidence: 99%
“…At 61 months, this patient had stable disease, whereas the boy had meningeal carcinomatosis presenting 1 month after surgery and died 7 months later. Karabekir et al [8] reported a 2-year-old female patient with a primary spinal AGG extending from T 9 to L 3 level. The patient presented with quadriceps weakness and was treated with partial resection followed by adjuvant radiotherapy (total dose of 40 Gy at 1.8 Gy per day).…”
Section: Discussionmentioning
confidence: 99%